Layanan Orientasi Berbantuan Multimedia untuk Meningkatkan Pengambilan Keputusan Studi Lanjut Siswa SMA - Aliyah Mufiqoh (WASIS : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study was to determine the level of decision making for further study to tertiary institutions by providing multimedia-assisted orientation services to students of class XII MIPA 8 SMA Negeri 1 Rembang.This research is a classroom action research conducted in two cycles. The subjects of this study were students of class XII.MIA.8 SMA Negeri 1 Rembang. The data collection technique used is a non-test technique using a questionnaire instrument and observation sheets. While the data analysis technique uses quantitative data analysis, namely descriptive percentages and qualitative descriptive analysis for qualitative data.The results showed that the provision of multimedia-assisted guidance services increased by 96.15% of students' ability to make decisions in the high and very high criteria. This increase was due to the provision of multimedia-assisted orientation services where students could obtain detailed and clear information about tertiary institutions.